2005
DOI: 10.1093/humrep/dei440
|View full text |Cite
|
Sign up to set email alerts
|

Warming Echovist contrast medium for hysterocontrastsonography and the effect on the incidence of pelvic pain. A randomized controlled study

Abstract: Warming of Echovist contrast media to body temperature is a simple and effective intervention in reducing discomfort at the time of HyCoSy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…It was reported that administration of a warm isotonic solution with a pressure below 70 mm Hg was shown to minimize intravasation. 14,15 There was significant difference between intravasation and endometrial thickness. 16 Venous intravasation is more frequent when the endometrial thickness is less than 6 mm.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It was reported that administration of a warm isotonic solution with a pressure below 70 mm Hg was shown to minimize intravasation. 14,15 There was significant difference between intravasation and endometrial thickness. 16 Venous intravasation is more frequent when the endometrial thickness is less than 6 mm.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, we may try to use different catheters to minimize the endometrial trauma or uterine pressure, such as the Leech Wilkinson cannula or even insemination catheters. It was reported that administration of a warm isotonic solution with a pressure below 70 mm Hg was shown to minimize intravasation . There was significant difference between intravasation and endometrial thickness .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we recommend to wait several minutes and to allow the building up of intrauterine pressure while injecting the gel foam, as tubal patency can still be demonstrated in some cases of suspected proximal block uni- or bilaterally. In the outpatient setting we routinely warm the gel to 37°C using a warming blanket to avoid thermal stimulation of the myometrial cells and to minimize uterine cramps [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Experiences from peritoneal dialysis (10) and laparoscopy (11) indicate that warm dialysis solution or air insufflations can reduce the severity of pain. A randomized study (12) on sonohysterography (SHG), another technique for examining tubal and uterine cavity pathologies, suggested that warming echoic contrast media to body temperature is a simple and effective intervention for reducing discomfort during the exam. Owing to the differences in SHG and HSG, namely the quantity and content of the media used, it is unknown whether this intervention would also have an impact on the pain levels experienced during HSG.…”
mentioning
confidence: 99%